2016
DOI: 10.1186/s12864-016-3365-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, phylogeny, and expression analysis of pectin methylesterases reveal their major role in cotton fiber development

Abstract: BackgroundPectin methylesterase (PME, EC 3.1.1.11) is a hydrolytic enzyme that utilizes pectin as substrates, and plays a significant role in regulating pectin reconstruction thereby regulating plant growth. Pectin is one of the important components of the plant cell wall, which forms the main structural material of cotton fiber. In this research, cotton genome information was used to identify PMEs.ResultsWe identified 80 (GaPME01-GaPME80) PME genes from diploid G. arboreum (A genome), 78 (GrPME01-GrPME78) PME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 55 publications
6
37
0
Order By: Relevance
“…As one of the pectin-modifying enzymes, the functionality of PME genes has been widely studied in many plant species, such as Arabidopsis [27], rice [28], flax [30], and cotton [31]. Here, 54 PME genes were identified in strawberry, and 53, 57, 66, 78 and 79 PME genes were found from rose, Chinese plum, peach, apple and pear, respectively (Additional file 2: Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the pectin-modifying enzymes, the functionality of PME genes has been widely studied in many plant species, such as Arabidopsis [27], rice [28], flax [30], and cotton [31]. Here, 54 PME genes were identified in strawberry, and 53, 57, 66, 78 and 79 PME genes were found from rose, Chinese plum, peach, apple and pear, respectively (Additional file 2: Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…[29], flax [30], and Asiatic cotton (Gossypium arboretum) [31]. All PME genes from those species contain a catalytically active zone PME domain, and some of them also comprise a pectin methylesterase inhibitor (PMEI) domain [27,28,30,31]. With expression assay, those studies found some candidate PME genes which have tissue-specific expression patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , Additional file 2 : Table S2). The PELs of Oryza sativa were located a long distance from those of the other plants, which might be related to different functions of these proteins between monocots and dicots [ 39 ]. All of the GhPELs exhibited the conserved Pec_lyase_C domain, with highly conserve Ca 2+ -binding, disulfide bonds, catalysis and substrate binding amino acid sites (Additional file 6 : Figure S1 and Additional file 7 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the PMEs expression levels at the developmental stage of fiber was observed using qRT-PCR. Predominant expression in fiber was during the secondary cell wall thickening stage suggesting tissue-specific expression patterns in cotton fiber [94].…”
Section: Characterization Of Specific Genes For Cotton Fibermentioning
confidence: 99%